Are rapid diagnostic tests more accurate in diagnosis of malaria compared to microscopy? - Batwala, Vincent; Magnussen, Pascal; Nuwaha, Fred (Malaria Journal, 2010)
Prompt, accurate diagnosis and treatment with artemisinin combination therapy remains vital to current malaria control. Blood film microscopy the current standard test for diagnosis of malaria has several limitations that necessitate field evaluation of alternative diagnostic methods especially in low income countries of subSaharan Africa where malaria is endemic.
Keywords: Microscopy; Malaria; Diagnosis